PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERBASIS MASALAH UNTUK KELAS VII SMP PADA MATERI HIMPUNAN - Komariyah, Siti (Universitas Pasir Pengaraian, 2016)
This study aims to generate math worksheets based on a valid and practical issues on the set material. This type of research was development of research (Research and Development), which consists of three stages of development of the definition (Define), the design (Design) and development (Develop). The subjects were students of class VII SMP N 2 Ujung Batu in the first semester of the school year 2015/2016. The instrument used in this study was validation questionnaire sheet and questionnaire sheet practicalities. Results of this research problem based worksheets. Based on test validity problem based worksheets that have been made to four people validator with some revisions and corrections then obtained an average score of problem-based validation results LKS was 3.52 categorized as very valid and based on the test the practicalities of using questionnaires, observation of the importance of the implementation of learning the average score of problem-based LKS practicalities result was 85% in the category of very practical. So it can be concluded that based LKS issue is very valid and very practical.